Gawr-Lakhnawati : a survey of historical monuments and sites in Bangladesh, SHMSB 002 - Husain, A. B. M., 1934-; Rashid, M. Harunur; Asiatic Society of Bangladesh (Dhaka : Asiatic Society of Bangladesh, 1997)
Gaur, ruined city in Malda District, India, on demarcation line between India and Bangladesh.
Includes bibliographical references (p. [167]-169) and index.
Keywords: Historic sites -- India -- Gaur; Monuments -- India -- Gaur; Gaur (India) -- Antiquities